Supplementation of Forage Sorghum with Meal Concentrate and Leucaena leucocephala on Goat Performance with Particular Reference to Meat Essential Fatty Acid Contents - MAKSIRI, Wanida; TUDSRI, Sayan; THIENGTHAM, Jamroen; PRASANPANICH, Somkiert (Walailak Journal of Science and Technology (WJST), 2016)
Forage sorghum, supplemented with meal concentrate or fresh leucaena on goat performance was studied, using 15 male crossbred Anglo-Nubian and Native goats. They were allocated into 3 treatments; Treatment 1: fresh forage sorghum with an amount of 2 % (as fed basis) meal concentrate of animal body weight; Treatment 2: fresh forage sorghum with an amount of 1 % (as fed basis) meal concentrate, and an amount of 1 % fresh leucaena of animal body weight, and Treatment 3: fresh forage sorghum with an amount of 2 % fresh leucaena of animal body weight, under the completely randomized design (CRD). The results showed that total dry matter intake was not significantly different among treatments. However, dry matter intake of forage sorghum was significantly different among treatments (p < 0.05), where the highest intake of roughage was found in treatment 3. Total crude protein intake was significantly different among treatments (p < 0.05), where the highest intake of crude protein was found in Treatment 1, affecting weight gain and average daily gain among treatments with significant difference (p < 0.05). The essential fatty acid contents of linoleic acid (C18:2 n-6; omega 6) and conjugated linoleic acid (C18:2 cis-9, trans-11, CLA) in the Longissimus dorsi muscle of goats were not significantly different while omega 3 fatty acid as linolenic acid (C18:3 n-3; omega 3) was significantly different among treatments (p < 0.05) where the highest amount (0.94 g/100 g fatty acid) was found in Treatment 3.